Efeito da antecipação da adubação nitrogenada na cultura do milho em sistema plantio direto - Nascimento, Flávia M.; Bicudo, Silvio José [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Rodrigues, José G. L.; Fernandes, Jairo C.; Furtado, Mariléia B. (Revista Brasileira de Ciencias Agrarias, 2012)
The main goal of this research was to evaluate the response of maize crop in succession to maize + oat crops, with the anticipation of the increasing doses of nitrogen application in the oat culture, in no-tillage system. The experiment was carried out under field conditions at FCA/UNESP, Botucatu Campus, São Paulo, Brazil. The experimental design was arranged in randomized blocks with four replications, in split-plots. The plots were the nitrogen doses applied on the oat crop (0, 20, 40 e 60 kg ha-1), and split-plots, the nitrogen doses applied in the cover (60, 80, 100 e 120 kg ha-1), divided into two different crop stages of the maize crop. The dry matter weight and the C/N ratio were assessed on the oat and maize crops. On the maize crop, the plant nitrogen was quantified before the first covering and 15 days after the second covering, when the dry matter weight of the maize plants was determined. After the harvest, the yield was also calculated. Results indicate that the maize development and yield under no-till system were related to the straw C/N ratio, and the maize crop response to the anticipated N fertilization anticipation varied according to the N doses and application periods. The dry matter weight of the maize plants were influenced by the rates and periods of N applications.
Effect of nitrogen fertilization anticipation on maize crop in no-tillage system
Keywords: Biomass; Chemical properties of soil; Crop succession; Zea mays